Resilience infrastructure for community in flood-prone areas in Kelantan / Ezzat Fahmi Ahmad, Ida Nianti Mohd Zin and Kartina Alauddin - Ahmad, Ezzat Fahmi; Mohd Zin, Ida Nianti; Alauddin, Kartina (2019)
The dependency of community on the functioning of infrastructure systems are very high particularly during flood disaster events. As flood disaster events are intensely and frequently happened in Kelantan, there is an extreme need to have resilience infrastructure systems. The resilience infrastructure systems can be define as an ability to resist, absorb, accommodate and recover from the effect of flood in a timely and efficient manner. In this case, the resilience infrastructure systems can be achieved through the implementation of resilience criteria (i.e. robustness; resourcefulness; rapidity; and redundancy). Therefore, the objective of this paper is to determine the most importance resilience criteria to strengthen infrastructure systems in flood-prone areas in Kelantan. Thus, cross-sectional survey was conducted among thirty-one (31) communities (government = 12; private sectors = 5; learning institution = 7; and communities = 7) who affected in flood-prone areas in Kelantan. A total 23 criteria (robustness = 5; resourcefulness = 6; rapidity = 6; and redundancy = 6) for resilience criteria were analysed by SPSS version 22 subjected to descriptive analysis. The result obtained from the analysis found that robustness is most significant criteria while availability of manpower is most significant sub-criteria for resilience infrastructure for community in flood-prone areas in Kelantan.